(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to explore the description of knowledge, attitudes and practices of handling Dengue Fever in the work area of ​​the Obi Island Clinic. The research design used in this study is descriptive research with a cross-sectional approach. The population in this study were all workers in the work area of ​​the Obi Island Clinic. The sample used in this study was selected based on the sampling method with a purposive sampling type. The instruments used in this study were demographic sheets and questionnaires regarding the Description of Knowledge, Attitudes and Practices with Handling Dengue Fever. Data analysis using a percentage formula for each variable which is then used to determine the cause. The level of knowledge of workers in the good category is 104 respondents (100%). The attitude of workers about DHF in the sufficient category is 101 respondents (97.1%) and the level of practice of workers in the good category is 101 respondents (97.1%). Conclusion, most workers in the Obi Island Clinic Work Area have good knowledge and practices related to DHF, although their attitudes towards DHF are mostly still in the sufficient category. Keywords: DHF, Knowledge, Practice, Attitud